2013
DOI: 10.1007/s10616-013-9566-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of primary cell culture from the temperate symbiotic cnidarian, Anemonia viridis

Abstract: The temperate symbiotic sea anemone Anemonia viridis, a member of the Cnidaria phylum, is a relevant experimental model to investigate the molecular and cellular events involved in the preservation or in the rupture of the symbiosis between the animal cells and their symbiotic microalgae, commonly named zooxanthellae. In order to increase research tools for this model, we developed a primary culture from A. viridis animal cells. By adapting enzymatic dissociation protocols, we isolated animal host cells from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Methods for assessing cell membrane integrity include dye exclusion assays [e.g. trypan blue, 73 , 95 ], Evan’s blue [ 176 , 177 ], propidium iodide [ 75 ], SYTOX green [ 85 ] and enzyme release assays (e.g. lactate dehydrogenase, LDH, [ 178 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methods for assessing cell membrane integrity include dye exclusion assays [e.g. trypan blue, 73 , 95 ], Evan’s blue [ 176 , 177 ], propidium iodide [ 75 ], SYTOX green [ 85 ] and enzyme release assays (e.g. lactate dehydrogenase, LDH, [ 178 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, standard conditions do not always support fungal or bacterial production of interesting secondary metabolites (Reich and Labes, 2017). To increase the availability of microbial biomass and minimize the environmental damage impacts of organismal collections, new strategies are needed to develop sustainable in vitro approaches for the cultivation of whole organisms or of individual cell types from targeted marine species (Rinkevich, 1999(Rinkevich, , 2005(Rinkevich, , 2011Barnay-Verdier et al, 2013;Ventura et al, 2018;Maristem COST Action 12 ). This is also of importance for sponges and corals, which host endosymbiotic intracellular microorganisms.…”
Section: Biotechnological Production Of Secondary Metabolitesmentioning
confidence: 99%
“…In cnidaria, attempts to establish permanent cnidarian cell lines have failed due to decreasing in vitro viability and proliferation (review in Rinkevich 2011 ). Despite this, short-term primary cultures have been used to understand the cellular mechanisms underlying fundamental cnidarian processes, such as symbiosis ( Barnay-Verdier et al 2013 ), calcification ( Domart-Coulon et al 2001 ; Mass et al 2012 ), thermal stress ( Nesa and Hidaka 2009 ), and regeneration ( Schmid and Alder 1984 ). These studies reported inconsistent results regarding survival, proliferation, and viability, reflecting the lack of standardized protocols (reviewed by Rinkevich 2005 , 2011 ).…”
Section: Introductionmentioning
confidence: 99%